PENGARUH KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN BERAS IKAN MAS DI UD. FAOMAKHODA DESA LOLOJUKHU KECAMATAN ULU IDANOTAE KABUPATEN NIAS SELATAN - Zebua, Erna Hati (Jurnal Ilmiah Mahasiswa Nias Selatan, 2024)
The purpose of this study was to determine the effect of product quality on customer satisfaction of carp rice at UD. Faomakhoda, Lolojukhu Village, Ulu Idanotae District, South Nias Regency. The type of research is a quantitative type, the population of this study is as many as 39 respondents. The sampling technique used is saturated sampling. This type of research data is a type of primary data while the source of this research data is from consumers by using questionnaires. The data analysis technique is simple regression analysis. The result of the study is that there is an influence of product quality on customer satisfaction of carp rice at UD. Faomakhoda, Lolojukhu Village, Ulu Idanotae District, South Nias Regency. The suggestion of this research is (1) to increase customer satisfaction, UD should be used. Faomakhoda gives a discount on the price of rice when consumers buy sacks. (2) in increasing customer satisfaction, UD should be. Faomakhoda promotes rice products according to customer needs.